CRISPR/Cas9-mediated base-editing enables a chain reaction through sequential repair of sgRNA scaffold mutations - Tsuyoshi Fukushima; Yosuke Tanaka; Keito Adachi; Nanami Masuyama; Akiho Tsuchiya; Shuhei Asada; Soh Ishiguro; Hideto Mori; Motoaki Seki; Nozomu Yachie; Susumu Goyama; Toshio Kitamura (Scientific Reports, 2021)
Abstract Cell behavior is controlled by complex gene regulatory networks. Although studies have uncovered diverse roles of individual genes, it has been challenging to record or control sequential genetic events in living cells. In this study, we designed two cellular chain reaction systems that enable sequential sgRNA activation in mammalian cells using a nickase Cas9 tethering of a cytosine nucleotide deaminase (nCas9-CDA). In these systems, thymidine (T)-to-cytosine (C) substitutions in the scaffold region of the sgRNA or the TATA box-containing loxP sequence (TATAloxP) are corrected by the nCas9-CDA, leading to activation of the next sgRNA. These reactions can occur multiple times, resulting in cellular chain reactions. As a proof of concept, we established a chain reaction by repairing sgRNA scaffold mutations in 293 T cells. Importantly, the results obtained in yeast or in vitro did not match those obtained in mammalian cells, suggesting that in vivo chain reactions need to be optimized in appropriate cellular contexts. Our system may lay the foundation for building cellular chain reaction systems that have a broad utility in the future biomedical research.